Sejarah Pemikiran Faith and Reason dalam Tradisi Reformed: dari Masa Abad Pertengahan hingga Masa Orthodoxy [A History of Thought on Faith and Reason in the Reformed Tradition: From the Middle Ages to the Period of Orthodoxy] - Stephen Rehmalem Eliata (Diligentia: Journal of Theology and Christian Education, 2022)
Research on historical thought of the Reformed tradition was started by Alexander Schweizer who proposed a method for reading history, namely centraldogmen. During its development, this method was received by a group of historians known as the Barthian tradition. In this tradition, the development of thought on the reformed tradition is considered to have been discontinued after John Calvin. These views surround the post-Calvinian theologians of the reformation tradition. Recent research tries to propose another method for reading history, namely by considering its continuity and discontinuity. With this new method, I intend to look at the history of the reformed tradition in the case of the relationship between faith and reason. This paper will discuss thoughts on the relationship between faith and reason from 3 different periods, that is the medieval period, the reformation period, and the orthodoxy period. From my analysis, I conclude that in the case of the relationship between faith and reason, there is a continuity of thought from the medieval period to the orthodoxy period. With this conclusion, the position of the Barthian tradition on reformed thinking needs to be re-evaluated.